Correlation between Interstitial Lung Disease Morphology Scores Based on High-resolution Computed Tomography Chest and Skin Fibrosis Degree Based on Modified Rodnan’s Skin Score on Systemic Sclerosis - Irma Hassan Hikmat; Suci Syamsiah Ramdhini; Hari Soekersi; Sumartini Dewi (Acta Medica Indonesiana)
Background: Systemic sclerosis (SSc) is a systemic autoimmune disease involving a multisystem. Modified Rodnan’s Skin Score (MRSS) is a gold standard for measuring skin fibrosis in SSc. In SSc, lung fibrosis disorders, especially interstitial lung disease (ILD), are the leading cause of mortality and often late in diagnosis. High-Resolution Computed Tomography (HRCT) Chest scan is a gold standard for evaluating ILD morphology, but its availability is limited. The degree of skin fibrosis based on MRSS in SSc can predict the presence of ILD in several studies but has not been widely studied in Indonesia. This study aimed to determine the relationship of the ILD morphology based on thoracic HRCT scan with the degree of skin fibrosis based on MRSS in SSc. Methods: This study is a retrospective analytic observational study with a cross-sectional design. The subjects of this study are SSc patients who had data of MRSS and HRCT chest scan from July 2019 to March 2020. Statistical analysis uses Spearman’s correlation test. Results: There were 42 study subjects, consisting of 41 women (97.6%) and one man (2.4%) with an average age of 39.50 years old (age range of 19 years to 60 years old). Correlation test results based on Spearman’s show a moderate correlation between the morphological score of ILD with MRSS with R = 0.429, which is significant (p = 0.005). Conclusion: There is a significant moderate correlation between the morphological scores of ILD based on HRCT chest and the degree of skin fibrosis based on MRSS in SSc.